Efficacy and safety of immunotherapy for head and neck squamous cell carcinoma: a meta-analysis of randomized clinical trials - Jiang, Cailing; Wang, Shuqin; Zhu, Lijun (Frontiers in Oncology, 2025)
BackgroundHead and neck squamous cell carcinoma (HNSCC) is one of the most common types of cancer worldwide and immune checkpoint inhibitors have shown favorable therapeutic effects in recurrent or metastatic or locally advanced head and neck squamous cell carcinoma (R/M/LA HNSCC). However, the effects of immunotherapy in HNSCC are still inconsistent because of complicating factors. This meta-analysis tries to provide a more precise assessment of the efficacy and safety of this integrated approach in HNSCC.MethodsWe conducted a systematic review and meta-analysis of randomized clinical trials according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guidelines. The outcomes were overall survival (OS), progression-free survival (PFS), and treatment-related adverse events (TRAEs). A total of 8 out of 2445 articles were analyzed, including 5067 HNSCC patients, including 823 and 4244 patients with LA HNSCC and R/M HNSCC.ResultsThe combined data revealed that immunotherapy has an apparent difference in OS (HR 0.86 95% CI 0.77-0.98) compared with standard of care (Soc, like fluoropyrimidine, methotrexate, docetaxel, or cetuximab) but was equal with the other treatment in PFS (HR 1.08, 95% CI 0.85-1.37). Furthermore, the occurrence of grade 3 or higher adverse events related to the drugs was lower than systematic therapy (OR 0.35, 95% CI 0.17-0.73).ConclusionsThe study has provided compelling evidence that immunotherapy is a significant benefit in OS for HNSCC patients, either R/M HNSCC or LA HNSCC, immunochemotherapy may benefit more for these patients, but double-agent immunotherapy showed no more benefit for R/M HNSCC patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/, identifier CRD42023471570.